Daily testing for contacts of individuals with SARS-CoV-2 infection and attendance and SARS-CoV-2 transmission in English secondary schools and colleges: an open-label, cluster-randomised trial - Young, BC; Eyre, DW; Peto, TEA; Kendrick, S; White, C; Smith, S; Beveridge, G; Nonnenmacher, T; Ichofu, F; Hillier, J; Oakley, S; Diamond, I; et al. (Elsevier, 2021)
Background School-based COVID-19 contacts in England have been asked to self-isolate at home, missing key educational opportunities. We trialled daily testing of contacts as an alternative to assess whether this resulted in similar control of transmission, while allowing more school attendance.